CXCL12/CXCR4 Axis Triggers the Activation of EGF Receptor and ERK Signaling Pathway in CsA-Induced Proliferation of Human Trophoblast Cells - Zhao, Hong-Bo (Public Library of Science, 2012)
INTRODUCTION: Our previous study has demonstrated Cyclosporin A (CsA) promotes the proliferation of human trophoblast cells. Therefore, we further investigate the intracellular signaling pathway involved in the CsA-induced proliferation of human trophoblast cells. METHODS: Enzyme-linked immunosorbent assay (ELISA) was performed to evaluate the regulation of CsA on CXCL12 secretion in human trophoblast cells. Immunofluorescence analysis and western blotting analysis were used to investigate the role of CXCL12/CXCR4 axis in the CsA-induced epidermal growth factor receptor (EGFR) phosphorylation in human trophoblast cells. 5-bromo-2′-deoxyuridine (BrdU) cell proliferation assay was performed to analyze the involvement of EGFR and its downstream extracellular signal-regulated protein kinase (ERK) signaling pathway in the CsA-induced proliferation of human trophoblast cells. RESULTS: Low concentration of CsA promoted the secretion of CXCL12, and recombinant human CXCL12 promoted the phosphorylation of EGFR in primary human trophoblast cells and choriocarcinoma cell line JEG-3. The inhibition of CXCL12 or CXCR4 by either neutralizing antibodies or small interfering RNA (siRNA) could completely block the CsA-induced EGFR phosphorylation. The CsA-induced proliferation of human trophoblast cells was effectively abrogated by the EGFR inhibitor AG1478 as well as the ERK inhibitor U0126, but not by the PI3K/PKB inhibitor LY294002. CsA promoted the activation of ERK in JEG-3 cells, which was markedly abrogated in the presence of CXCL12 siRNA, or CXCR4 siRNA, or AG1478. CONCLUSIONS: CsA may promote EGFR activation via CXCL12/CXCR4 axis, and EGFR downstream ERK signaling pathway may be involved in the CsA-induced proliferation of human trophoblast cells.